Fluid dynamics in water exit - Kim, Seong Jin (대한기계학회, 2019)
Interactions between a solid body and a liquid-air interface play an important role in multiphase flows, which is also crucial in animal behaviors and numerous industrial applications. Among diverse interfacial phenomena, liquid-exit is one of the fundamental problems to understand the fluid-solid interaction when a solid object exits out of liquid toward air. In the present paper, this liquid-exit behavior will be discussed for a liquid column stretched by a solid sphere moving with a constant acceleration. The liquid column dynamics are described by modifying the classical theory of capillary instability called Plateau？Rayleigh instability to include the acceleration contribution. And then, the dynamics of the stretched liquid column are found to change from capillarity-driven to inertial-driven with increasing the sphere acceleration.
Keywords: 출수(Water exit); 표면장력(Surface tension); 플래토-레일리 불안정성 (Plateau？Rayleigh instability); 유-고체 상호작용(Fluid-solid interaction); 다상유동(Multiphase flow)